Sosialisasi Beasiswa Kampus : Upaya Memperluas Akses dan Kesempatan Bagi Mahasiswa Berprestasi - Rekha Widiawati; Farida Nabilah; Isthifaiyayyatul Qudsi; Rahayu Mardikaningsih; Mila Hariani; Yeni Vitrianingsih; Eli Retnowati; Eli Masnawati; Utami Puji Lestarie (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The promotion of campus scholarships is one step in introducing the campus to the wider community and providing opportunities for outstanding students to take advantage of the opportunities offered. The method used in socializing this scholarship is using the ABCD method. The results of the socialization carried out had a positive impact on both parties, from the Sunan Giri University institution which was able to invite students to join together, as well as providing the wider community with the opportunity to take advantage of the scholarship program offered.